Modeling and analyzing of nonlinear dynamics for spur gear pair with pitch deviation under multi-state meshing. (September 2021) - Liu, Pengfei; Zhu, Lingyun; Gou, Xiangfeng; Shi, Jianfei; Jin, Guoguang
Highlights: The characteristic function of pitch deviation for spur gear pair is established. The influence of pitch deviation on meshing state of spur gear pair is analyzed. A nonlinear dynamics model of spur gear pair with pitch deviation is established. Effect of pitch deviation on gear stability revealed by dynamic meshing force. Effect of pitch deviation on nonlinear dynamics of spur gear pair is examined. Abstract: The pitch deviation of gears caused by machining leads to corner contact in actual meshing process. In order to study the influence of the pitch deviation on motion characteristics of the spur gear pair, meshing state functions are constructed to reflect multi-state meshing including mesh-in at corner contact, mesh-out at corner contact, single and double pair drive-side teeth mesh, single and double pair back-side teeth contact and tooth disengagement. The nonlinear dynamics model of spur gear pair with pitch deviations under multi-state meshing is established. Variation laws of dynamic meshing forces and meshing states for the spur gear pair are analyzed. The influence of main parameters on nonlinear dynamics of the spur gear pair with pitch deviations is investigated. Results indicate that the pitch deviation results in complex periodic motion as a short-period error in spur gear pair. It mainly affects transmission stability of the spur gear pair by changing meshing states. This investigation provides a theoretical basis for the parameter design of the spur gear transmission system and the influence of pitch deviation in other gear transmission systems.